DIRECTORS’ COMPENSATION & FINANCIAL STATEMENT FRAUD: A COMPARATIVE STUDY OF CHINA AND THE US - Jain, Juhee (2022)
Financial statement fraud (FSF), generally committed by personnel in high ranks commanding substantial power, is regarded as one of the costliest corporate frauds which has affected both developed and developing nations. One of the reasons for the occurrence of FSF is the divergence in interests of the management (agents) and shareholders (principals). Agency theory propounds implementation of adequate compensation for achieving the alignment of interests of agents and principals. However, compensation is a double-edged sword, which may control or aggravate the incidence of FSF. Existing research has, primarily, focused on earnings management/restatement/FSF and its linkages with executive compensation. However, such analysis does not give a full picture, as directors (acting as agents of shareholders) are key monitors of the management and if they are effective in their monitoring function, then the incidence of FSF can be controlled. Hence, it is imperative that the directors’ interests are well aligned with those of the shareholders. Thus, this research attempts to view the incidence of FSF from the perspective of directors. Herein, an attempt is made to examine the causal relationship between FSF and directors’ compensation and shareholding.